Cardio specific Troponin I in patients with Aortic stenosis (Bangladesh Journal of Pathology, 2009)
To evaluate the association of Cardio specific Troponin I (CTnI) and aortic stenosis. Cross sectional study was conducted among 20 aortic stenosis patients and 20 control groups. A structured questioner and checklist was used to collect data through face to face interview, Echocardiography findings, and laboratory estimation of cTnl. A total 20 patients and 20 healthy control subjects were investigated for cTnl. cTnl level was within normal physiological limits in all the control subjects. The mean value was 0.02±00. The mean cTnl level in Aortic stenosis patients were 0.67±0.81. EJection fraction of Aortic stenosis patients were normal, indicating that cases yet not develops complication (eg; Heart failure). The cTnl in control group and Aortic stenosis patients shows significant difference of mean (p < 0.001). cTnl level in Aortic stenosis patients increases in absence of heart failure indicating that it can expose cardiomyocyte injury prior to the development of over Left ventricular dysfunction. So that, serial monitoring of cTnl could help clinician to give definitive treatment before development of complications. Keywords: Cardiospecific Troporin I. Aortic Stenosis.   doi: 10.3329/bjpath.v24i1.2875 Bangladesh J Pathol 24 (1) : 9-11